Abscission of Control Pollinated Coconut Fruits: Preliminary Investigations into the Possible Role of Ethylene - Nipah, J. Owusu; Safo-Kantanka, O.; Dickinson, Matthew J. (International Coconut Community Journal, 2010)
Recent advances in the spread of the Cape St Paul Wilt disease (CSPWD) necessitate a more rapid development of tolerant coconut types. Control pollination is the main method for producing legitimate coconut seeds for such breeding purposes. However, the process of bagging causes severe nut drop or abscission. Many scientists have implicated hormones as the primary regulators of organ abscission; with ethylene being particularly implicated. Unlike other plant hormones, which are mainly produced in other parts and transported to influence target organs, the production of ethylene could be initiated within the same organ, such as the fruit. This study was therefore undertaken to investigate the possible involvement of ethylene in abscission after control pollination. Pollen from Vanuatu Tall (VTT) variety was used to cross emasculated Malayan Yellow Dwarf (MYD) inflorescence after isolation with bags. Trials were laid out in Completely Randomised and Split Plot designs, with specified replications. Two ethylene inhibitors, namely aminoethoxyvinylglycine (AVG) and silver thiosulphate (STS) were used. Five concentrations of AVG ranging from 2mg/l to 30mg/l were applied to inflorescences during and after bagging. AVG concentrations higher than 2 mg/l resulted in significant reduction in abscission. Fruit yields up to five times that of ordinarily bagged treatments without AVG were recorded. Four concentrations of STS ranging between 0.5mM – 10mM applied in similar manner, however, did not result in any significant reduction in abscission. The results from AVG application strongly suggest the involvement of ethylene in the abscission of control pollinated coconut fruits.